IMPLEMENTASI AKAD WAKALAH BIL UJRAH DALAM MEKANISME TIKTOK AFFILIATE PERSPEKTIF HUKUM EKONOMI SYARIAH - Rafli Saidi; Cucu Susilawati; Nasrudin Nasrudin (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2026)
The development of digital technology has shifted consumer behavior from conventional to online transactions, triggering the emergence of social commerce innovations such as TikTok Affiliate. Although it provides economic convenience, this practice requires further review due to the risk of dishonest promotions for the sake of commissions, which potentially violates the values ​​of integrity in Islamic economics. This study aims to analyze the working mechanism of TikTok Affiliate and review its implementation and compliance with the principles of Islamic Economic Law, particularly through the perspective of the wakalah bil ujrah contract. The research method used is empirical juridical with a descriptive approach, referring to primary interview data and secondary literature studies. The results show that the TikTok Affiliate mechanism meets the requirements of muamalah in Islam. In practice, the wakalah bil ujrah contract can be implemented, where the seller (muwakkil) authorizes the affiliate (wakil) to promote the product in exchange for a transparent and pre-agreed commission (ujrah). Income from this program is considered legitimate according to Islamic law and the DSN-MUI Fatwa as long as the parties prioritize the principle of honesty and comply with the agreed contractual limits.